2014
DOI: 10.1021/ef4021262
|View full text |Cite
|
Sign up to set email alerts
|

Release of Chlorine and Sulfur during Biomass Torrefaction and Pyrolysis

Abstract: The release of chlorine (Cl) and sulfur (S) during biomass torrefaction and pyrolysis has been investigated via experiments in two laboratory-scale reactors: a rotating reactor and a fixed bed reactor. Six biomasses with different chemical compositions covering a wide range of ash content and ash-forming elements were torrefied/pyrolyzed in the temperature range of 150−500 °C. The relative release of chlorine and sulfur was calculated based on mass balance and analysis of the biomass before and after torrefact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 35 publications
13
89
0
Order By: Relevance
“…It is noteworthy that sulfur contents had a trend to decrease with torrefaction for both RH and W-RH. Similar results could be found in other researches (Chen et al, 2012a,b;Saleh et al, 2014).…”
Section: Influence Of Pretreatment On Fuel Characteristicssupporting
confidence: 92%
“…It is noteworthy that sulfur contents had a trend to decrease with torrefaction for both RH and W-RH. Similar results could be found in other researches (Chen et al, 2012a,b;Saleh et al, 2014).…”
Section: Influence Of Pretreatment On Fuel Characteristicssupporting
confidence: 92%
“…Knudsen et al (2004) indicated that the release of sulfur begins with the cysteine and methionine units (two main S-containing precursors for plant protein) which start to decompose at 178 and 183 °C, respectively (Knudsen et al 2004). Similar results were found by Saleh et al (2014). In their study, the release of sulfur from straw and miscanthus was approximately 20% at 250 °C and then gradually increased to approximately 50% at 350 °C.…”
Section: Ultimate Analysissupporting
confidence: 57%
“…There was evidence that at the working temperatures of the torrefaction experiments (300 • C) in this study, chlorine from the plastic materials should have been released as HCl (Saleh et al, 2014). Further, Bar-Ziv and Saveliev (2013) measured HCl in the torrefaction gas stream that was equivalent to the chlorine reduction in the solid phase.…”
Section: Chlorine Removalmentioning
confidence: 55%